“Vietnamese time bomb.” Pseudomonas, we didn’t start the fire ,a gram negative Non fermatative bacilli ,works on blue. [Resistance pattern observed in Sree Mookambika Institute of Medical Sciences, Kulasekharam which varies from Hospital to Hospital (24-4-2020 to 7-4-2021)]a study. - Jeevan, Dr.Sabi (Jour Med Resh and Health Sci, 2021)
Proteobacteria groups: Gamma group –Pseudomonas 2021 ICD-10-CM Diagnosis Code B96.5 Pseudomonas (aeruginosa) (mallei) (pseudomallei) as the cause of diseases classified elsewhere .B96.5 is a billable/specific ICD-10-CM code that can be used to indicate a diagnosis for reimbursement purposes. Pseudomonads are aerobic gram negative bacilli belong to class gammaproteobacteria.Ubiquitous in soil ever moist environment, wash cloth,swimming pool ,hot tub and contact lens solutions. Its inherent resistance to a wide range of antimicrobial agents so rarely casuse disease. Has fimbriae and other adhesins and several virulence factors .Toxins and enzymes like lipid A in cellwall triggers fever ,vasodilation ,inflammation shock and other symptoms. A mucoid polysaccharide capsule and its role in cystic fibrosis patients & protects from phagocytosis and in burns victims. The ability of pseudomonas to form biofilm by metabolizing the many drugs and pump them out through antiports.2